2022
DOI: 10.17509/alsuniyat.v5i1.44843
|View full text |Cite
|
Sign up to set email alerts
|

Why is Masdar Important? An Investigating of Masdar and its Translation

Abstract: The variety of Arabic word forms has presented difficulties and challenges in its translation. The Arabic word form or sigat requires the translator to take the most appropriate technique to produce a good and correct translation into Indonesian or vice versa. Masdar's translation often receives less attention which causes errors in the translation of various texts. There are many forms of masdar in the Qur'an, which are used as references in Arabic grammar. This study aims to know and understand the types and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In morphosemantics, in addition to changing word building, it also has implications for changes in meaning resulting from morphological processes (Ghozali & Khoiriyatunnisa, 2021). Morphology according to Al-Ghalayaini is defined as the study of basic words to gain an understanding of the various forms of words in Arabic, including changes and development of these words (Nurmala et al, 2022;Ruhmadi & Al Farisi, 2023). There are several aspects of morphology including shighat (Miftahuddin, 2015), wazan-wazan tashrif (patterns) (Irawan, 2020), a collection of word forms consisting of archetypes, lawashiq (affixes) (Ghalayain in Asy'ari, 2016), and zawaid (Hassan in Kosim, 2020), and word derivation (Anis in Ruslan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In morphosemantics, in addition to changing word building, it also has implications for changes in meaning resulting from morphological processes (Ghozali & Khoiriyatunnisa, 2021). Morphology according to Al-Ghalayaini is defined as the study of basic words to gain an understanding of the various forms of words in Arabic, including changes and development of these words (Nurmala et al, 2022;Ruhmadi & Al Farisi, 2023). There are several aspects of morphology including shighat (Miftahuddin, 2015), wazan-wazan tashrif (patterns) (Irawan, 2020), a collection of word forms consisting of archetypes, lawashiq (affixes) (Ghalayain in Asy'ari, 2016), and zawaid (Hassan in Kosim, 2020), and word derivation (Anis in Ruslan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Muslims can memorize and practice the contents of the Quran properly, correctly, and adequately (Nurmala et al, 2022). For him, because the reward for the servant who reads the Quran alone is very greatsignific, ant though when a person listens to the reading of the Quranic verses, it is the same as the reward as he reads poetrytrys of the Quran.…”
Section: Introductionmentioning
confidence: 99%
“…No research has been found on fi'l muta'addi regarding translation technique and it's quality, especially in the text of Prophet Muhammad's life journey. Studies that previous researchers on Arabic translation techniques have conducted include the study of Mashdar translation(Nurmala, 2022). However, in the study, the researcher did not link the study of Masdar's translation technique with the quality of translation.…”
mentioning
confidence: 99%